Increased HIV Transmissions With Reduced Insurance Coverage for HIV Preexposure Prophylaxis: Potential Consequences of Braidwood Management v. Becerra. (16th March 2023) - Paltiel, A David; Ahmed, Ali R; Jin, Elena Y; McNamara, Meredithe; Freedberg, Kenneth A; Neilan, Anne M; Gonsalves, Gregg S
Abstract: A US federal court recently ruled against requiring health insurers to cover human immunodeficiency virus (HIV) preexposure prophylaxis (PrEP) under the Affordable Care Act. For every 10% decrease in PrEP coverage resulting from this ruling among US men who have sex with men, we estimate an additional 1140 HIV infections in the following year in that population. Abstract : A US federal court ruling against requiring insurance coveragefor HIV pre-exposure prophylaxis under the Affordable Care Act may result in over2, 000 preventable primary HIV infections among US men who have sex with men in thecoming year.